CITRA PEREMPUAN DALAM PUISI ”PEREMPUAN PENDOA” KARYA NADIR - Nurhalimah, Nurhalimah; Yunita, Shepia; Rohmah, Dita Rizqi Mawadatur; Julianto, Indra Rasyid (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
Poetry is a form of literary expression that contains the beauty of language and deep meaning, often reflecting human experiences, emotions, and thoughts. Through the use of metaphors, symbols, and distinctive language structures, poetry has the ability to convey complex and emotionally evocative messages to the reader. Therefore, poetry analysis is important to uncover hidden meanings, understand the message that the poet wants to convey, and explore the social and cultural context behind it. This study aims to analyze the image of women in Nadir's poem Perempuan Pendoa, focusing on the inner struggles experienced by female characters. The issue raised is how this poem reflects women's strengths and vulnerabilities in a patriarchal social context. The methods used are heuristic and hermeneutic analysis, which allows for an in-depth understanding of the structure of language and the meanings it contains. The results of the study show that this poem depicts the duality of women's emotions, where fortitude goes hand in hand with doubt, and reflects the challenges faced by women in expressing themselves. This analysis confirms that poetry is not only an art form, but also a medium to convey women's experiences and struggles, as well as a reflection of the social realities that affect their lives.